The Silently Shifting Semicolon - Marino, Daniel; Millstein, Todd D.; Musuvathi, Madanlal; Narayanasamy, Satish; Singh, Abhayendra; Musuvathi, Madan (1st Summit on Advances in Programming Languages, SNAPL 2015, May 3-6, 2015, Asilomar, California, USA, 2015)
Memory consistency models for modern concurrent languages have largely been designed from a system-centric point of view that protects, at all costs, optimizations that were originally designed for sequential programs. The result is a situation that, when viewed from a programmer's standpoint, borders on absurd. We illustrate this unfortunate situation with a brief fable and then examine the opportunities to right our path.